Respostas bioquímicas em carpas (Cyprinus carpio) expostas a duas formulações comerciais de inseticidas em condições de lavoura de arroz e em laboratório - Clasen, Bárbara Estevão (2012)
The pesticides are substances widely used in agriculture, because it enhances productivity. However, its excessive and disordered use has caused different impacts on the environment. Therefore, this study investigated the effects in carps (Cyprinus carpio) exposed to carbofuran (two agricultural years) and fipronil (one agricultural years) in rice field condition for 7, 30 and 90 days, as in laboratory condition for 30 days. In addition, evaluation of growth fish parameters and pesticides concentrations in the experimental water. The SOD activity in liver increased after 7, 30 and 90 days of exposure to 50.0 μg/L of carbofuran under rice field condition in the years 1 and 2. A decrease in hepatic CAT activity was showed after 30 days of exposure in both experimental years. GST activity in liver showed a significant increase after 30 days of exposure, and decrease after 7 and 90 days in both experimental years. Protein carbonyl levels decreased after 90 days in the first experimental year. During the second experimental year the protein carbonyl levels were reduced in all the periods of exposure. In both experimental years TBARS increased significantly in the brain after all periods studied, while in liver and muscle significant increase occurred only after 30 and 90 days of exposure. The carbofuran did not affect fish growth compared to control group in both experimental years. The SOD activity in liver increased whereas the hepatic activity of CAT was inhibited at 7, 30 and 90 days of exposure to fipronil. There were no changes in GST activity in all experimental periods. The protein carbonyl levels increased after 30 and 90 days of exposure, as TBARS levels increased in all the analyzed tissues (muscle, liver and brain) and periods analyzed. Regarding the growth of carp during the experimental period, no significant differences were observed in fish treated with fipronil when compared with the control group. In a third study were performed evaluations in carp exposed to the carbofuran and fipronil for 30 days in laboratory conditions. An increased in TBARS liver, muscle and brain of fish as the protein carbonyl levels in the liver after exposure to both insecticides tested. Liver CAT activity remained unaltered, as GST in liver, muscle and brain after exposure to carbofuran fipronil. The antioxidant enzymatic system showed an increase of GSH in the liver after exposure to both insecticides, whereas in the brain and muscle are not altered. Acid ascorbic levels demonstrated increased in liver, muscle and brain after exposure to carbofuran. After exposure to fipronil this parameter were increased only in the brain. The AChE activity was inhibited in brain and muscle of fish after exposure to both insecticides. The results from these studies show that carbofuran and fipronil cause disturbances in biochemical parameters of fish exposed in rice field as in laboratory condition. These studies revealed the occurrence of oxidative stress, without affecting the survival of fish, but can be harmful to your health.